The Information Technologyas a Factor for Improving the Teaching-Learning Process in Distance Education at a University - García Muñoz Aparicio, Cecilia; Piña Gutiérrez, José Manuel; Ancona Alcocer, María del Carmen; Navarrete Torres, María del Carmen (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
This article shows the impact that new technologies have had, whether they be information and / or communication in Universidad Juárez Autónoma de Tabasco [UJAT], which have revolutionized the way we perceive, access and transmit knowledge conforming day by day with a part in the teaching-learning process as well as its use in the classroom, both students and teachers, because they both benefit in the use of ICTs in education, and that learning is stimulated continuously, being part of today's culture for the development of the universities that have launched distance education programs to reach all places. The methodology used is documentary, aiming to show the progress of the university.